Online optimisation of the CLIC drive beam bunch train recombination at CTF3 - Gamba, D (2016)
The Compact Linear Collider (CLIC) design is the leading alternative for a future multi-TeV e+e− linear collider. One of the key aspects of the design is the use of a Drive Beam as power source for the acceleration of the colliding beams. This work is focused on the optimisation of the set-up and the operations of the CLIC Drive Beam recombination at the CLIC Test Facility (CTF3) at CERN. The main effects that may affect the beam quality during the recombination are studied, with emphasis on orbit, transverse dynamics and beam energy effects. A custom methodol- ogy is used to analyse the problem, both from a theoretical and a numerical point of view. The aim is to provide first-order orbit and transverse optics constraints, which can be used as guidelines during the set-up of the beam recombination process. The developed techniques are applied at the CTF3, and the results are reported. The non-linear beam energy effects have been investigated by means of MAD-X simulations. The results show that these effects might be critical for the quality of the recombined beam. A proper non-linear correction turns out to be necessary, especially in the Delay Loop (DL). An alternative DL optics is proposed to mitigate the non-linear energy effects using only linear elements, in contrast with the original design, which relies on sextupoles. A set of tools for the online control and optimisation of the beam orbit and dispersion has been implemented, deployed and used for the optimisation of the Drive Beam produc- tion at CTF3. Particular effort was put into the development of a generic linear feedback application, which is presented in this work. Thanks to the generality of the problem and its implementation, the feedback has been successfully used for a series of optimisations of the beam at CTF3. A collection of experimental results, focused on the Drive Beam recombination process, is presented and discussed.